Analysis of Medan Selayang Village Service Information System in Optimizing Local Tax Revenue - Dwi Salsabila Ilham; Oktarini Khamilah Siregar (Finance : International Journal of Management Finance, 2025)
This think about points to decide the arrive and building charge collection framework on the territorial wage of Medan Selayang. Arrive and Building Charge (PBB) in Indonesia may be a central charge since its administration is fully submitted to the Central Government, in spite of the fact that the ultimate result within the shape of income is returned to the locale with a expansive rate. This investigate employments clear examination which is utilized in clarifying arrive and building assess on neighborhood income in Medan Selayang. The information utilized is essential information within the frame of interviews with staffing pioneers with respect to the common depiction of the investigate area. The comes about of the charge income are isolated between the Central Government and the Rule / City Government and the Common Government, but most of the charge income is given to the Rule / City Government as the significant territorial salary. The comes about of the consider found that the usage framework of arrive and building charge collection at the Medan Selayang Town Head Office was thought to be compelling and effective.